(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: A combined approach for glaucoma coexistent with cataract has been always interesting for ophthalmologists since these diseases are often found together in patients. Purpose: To investigate the clinical efficacy and safety of combined phacoemulsification and Alcon EX-PRESS glaucoma filtration device (GFD) implant procedure and to develop indications for implantation of 50-?m and 200-?m devices. Materials and Methods: The study involved 115 primary open-angle glaucoma patients (115 eyes) with cataract divided into 3 groups depending on the type of glaucoma surgery. Group 1 involved 30 patients (30 eyes) who underwent phacoemulsification combined with the 50-?m GFD implant procedure. Group 2 involved 30 patients (30 eyes) who underwent phacoemulsification combined with the 200-?m GFD implant procedure. Group 3 included 55 patients (55 eyes) who underwent phacoemulsification combined with nonperforating deep sclerectomy. The mean preoperative intraocular pressure (IOP) in Group 1, Group 2 and Group 3 was 22.9±2.9 mmHg, 22.8 ± 3.5 mmHg (р1/2 > 0.05), and 22.6 ± 3.4 mmHg (р1/3 > 0.05; р2/3 > 0.05), respectively. Results: At 24 months postoperative, the mean IOP in Group 1, Group 2 and Group 3 was 15.4 ± 1.7 mmHg, 16.1 ± 2.1 mmHg (р1/2 > 0.,05), and 18.8 ± 1.9 mmHg (р1/3 < 0.05; р2/3 < 0.05), respectively. The number of postoperative complications in Group 1 and Group 2 was statistically significantly lower than that in Group 3. Conclusion: Phacoemulsification combined with the EX-PRESS glaucoma filtration device implant procedure is an efficacious and safe surgical technique for stabilization of glaucoma process. The 50-?m Alcon EX-PRES GFD implantation is indicated in stage I or stage II of unstabilized glaucoma with subcompensated IOP. The 200-?m Alcon EX-PRESS GFD implantation is indicated in stage III or stage IV of unstabilized glaucoma with decompensated IOP.